Footprints of "Experiment" in Early Arabic Optics - Kheirandish, Elaheh (Early science and medicine, 2009)
AbstractThis study traces the early developments of the concept of experiment with a view of extending the subject in both content and approach. It extends the content of the subject slightly backward, prior to the methodological breakthroughs of the Optics of Ibn al-Haytham (Alhazen or Alhacen, d. ca. 1040), which are credited as a "significant landmark in the history of experimental science." And it extends the approach to the subject slightly forward, from the premise that early science was "largely carried out in books," to a close examination of the books through which the footprints of 'experiment' may be traced. The point of departure is the Optics of Ahmad ibn 'Ī;sā, a revealing text for the early developments of concepts such as 'demonstration' and 'experiment', and one through which some modern discussions are examined and extended with reference to this and other historical sources.